Induced resistance of oil palm seedlings against basal stem rot using calcium, copper and salicylic acid - M. Shahul Hameed, Rahamath Bivi (2013)
The oil palm (Elaesis guineensis) tree, which belongs to the Palma family, is one of the most versatile crops in tropical countries. Oil palm was the major commodity inside the Malaysian agriculture sector. Malaysia is presently the world’s leading exporter of oil palm and it was second only to soybean as the major source of vegetable oil. However, a soil fungus pathogen, Ganoderma boninense, which causes basal stem rot (BSR) in the oil palm’s trunk, destroys thousands of hectares of plantations in Southeast Asia every year. Thus far there was no conclusive method for early detection of BSR in order to control the disease from spreading in the plantation. Plant nutrient and hormone are vital variables and modifying these as a control method may prevent Ganoderma attack. The limited nutrients and hormone of plants can trigger lignin degradation and conversely ensuring they are available for oil palm may limit the rot. These nutrients could conceivably be supplied by foliar and soil application with a view to control the disease in addition to them being used as fertilizers. Fertilizers are added which hold some of these minerals, but the point here is to control the disease and also improve the growth of the oil palm. The objective of the present work is to study calcium (Ca), copper (Cu) and salicylic acid (SA) application in oil palm and to determine their potential as fertilizers to control against Ganoderma boninense in vitro and in vivo. The in vitro effects of single and combined application of Ca, Cu and SA were evaluated on growth and sporulation of G. boninense. In poison medium test, T7-(Ca+Cu+SA) showed effective control of G. boninense in-vitro with EC₅₀ and EC₉₀ values of 1500+150+150 ppm and 2000+200+200 ppm, respectively. However, in dipping test, T7-(Ca+Cu+SA) indicates effective control of G. boninense at low concentrations, 200+50+50 ppm as shown by EC₉₀ analysis. Pre-treatment of Ganoderma-infected rubber wood block with 500 ppm Ca+50 ppm Cu+50 ppm SA reduced the number (20.14%) and (0.8 g) weight of basidiocarp compared to the control. This was followed by a significant reduction in weight loss of the Ganoderma-infected rubber wood block (41.85%) suggesting the inhibition of the degradative enzymatic activity of the fungus. The mixture of Ca, Cu and SA had potential to suppress growth of G. boninense under in vitro condition. The effect of Ca, Cu and SA further tested in a glass house for about 9 months for their efficacy in controlling BSR in oil palm seedlings through foliar and soil drenching by control of water application. As tested in oil palm seedlings inoculated with G. boninense, both of them, alone and in mixture suppressed G. boninense compared to the control. Not only they delayed the onset of BSR symptoms, but also promoted the growth of the seedlings. The application of Ca, Cu and SA together reduced disease incidence most effectively and was recorded reduction at 81.0% and followed by BSR disease incidence reduced for mixture of Ca and SA; a mixture of Cu and SA; and Ca alone respectively with a 76.1% reduction. In addition, treatment with Ca+Cu+SA increased the levels of the defense related enzymes phenolics, peroxidase, lignin and hydrogen peroxide on oil palm seedling tissues. Plant growth and antibiosis, plant nutrient and hormone enhanced the resistance in plants through the induction of defense enzymes in the oil palm seedlings.